DOMINASI PERAN WALI NAGARI DALAM PENDIRIAN BADAN USAHA MILIK NAGARI (BUMNAGARI) - Zamhasari,; Suryaningsih,; Tengku Fahrul Gafar,; Rianda Prima Putri, (Jurnal Cakrawala Ilmiah, 2023)
This study aims to analyze the role of the nagari guardian in the establishment of BUMNagari. By using the situational theory of Hersey and Blanchard as well as with descriptive qualitative methods, it was found that the nagari guardian has a dominant role (directive) in the establishment of BUMNagari with high direction. The high direction of the nagari guardian can be seen from the initiative to establish BUMNagari, determining the business of BUMNagari, and the amount of capital participation in BUMNagari. The role of the nagari guardian is so dominant because the establishment of BUMNagari is the desire of the Wali Nagari and not based on the wishes of the community, the determination of BUMNagari's business is also based on the wishes of the nagari guardian not based on the economic business potential of the nagari, and the determination of the amount of capital participation in BUMNagari is also the decision of the nagari guardian as the holder of financial power in the nagari not based on the results of the business analysis study.